The influence of treatment access regulation and technological resources on the mortality profile of acute biliary pancreatitis - Carvalho,Francisco Ribeiro de (2008)
PURPOSE: The influence of treatment access regulation and technological resources on the mortality profile of acute biliary pancreatitis (ABP) was evaluated. METHODS: The cases seen in a tertiary hospital were studied during two periods of time: 1995-1999 and 2000-2004, i.e., before and after the implementation of medical regulation. RESULTS: Among the 727 patients with acute pancreatitis, 267 had ABP and were classified according to APACHE II scores. The cases being referred to the tertiary hospital decreased from 441 to 286 (p < 0.001). The patients' profile regarding age, gender, severity, cholestasis incidence and mortality were similar during the first and second periods of study (n = 154 and n = 113, respectively). The number of patients with hematocrit > 44% was smaller during the second study period (p<0.002). The use of magnetic resonance cholangiography, videolaparoscopic cholecystectomy, and access to the ICU were found to be more frequent during the second study period. Regarding the deaths occurring within 14 days of hospitalisation, 73.4% and 81.3% were observed during the first and second study periods, respectively. CONCLUSION: Since the improvement in clinical and technological approach was not enough to modify the mortality profile of ABP, further studies on the treatment of inflammatory responses should be carried out.